G371(P) Barriers and facilitators to paediatric symptom management at end-of-life: results from a systematic review and meta-analysis. (25th October 2020) - Greenfield, K; Holley, S; Schoth, DE; Harrop, E; Bayliss, J; Howard, RF; Johnson, M; Liossi, C
Abstract : Background: Managing symptoms, including pain, at end-of-life for infants, children and young people is challenging due to the broad spectrum of life-limiting or life-threatening conditions, and also differing care needs depending on patients' age. The UK National Institute for Health and Care Excellence (NICE) highlights pain management in paediatric palliative care as a research priority. A clearer understanding of these challenges could inform the development of effective interventions. Aims: We aimed to conduct a mixed-methods systematic review and meta-analysis investigating the barriers and facilitators experienced by patients, carers and healthcare professionals managing symptoms in infants, children and young people at end-of-life. Methods: PROSPERO, Cochrane Library, CINAHL, MEDLINE, PsycINFO, Web of Science Core Collection, ProQuest Dissertations & Theses Database, Evidence Search and OpenGrey were searched from the inception of each database for qualitative, quantitative or mixed-methods studies that included data regarding barriers or facilitators to paediatric end-of-life symptom management from patients, family carers or healthcare professionals. Search terms were derived from a thorough reading of relevant literature and in discussion with a medical librarian. Data extraction, quality appraisal, and narrative thematic synthesis were undertaken for all eligible studies, with meta-analysis also performed where data permitted. Results: We identified 34 quantitative, 19 qualitative and 17 mixed-methods eligible studies of medium-low quality (assessed using GRADE-CERQual). Themes were generated around the barriers and facilitators experienced by family carers (Treatment efficacy, Treatment side-effects, Healthcare professionals' attitudes, Hospice care, Homecare, Families' symptom management strategies) and Healthcare professionals (Medicine access, Treatment efficacy, Healthcare professionals' demographics, Treatment side-effects, Specialist support, Healthcare professionals' training, Health services delivery, Homecare). Only one study included patients' views. Caring at home for a child was reported as a barrier to symptom management by between 22 and 24% of participants (pooled weighted mean of 0.244, k = 3, n = 197, 95% CI = 0.177–0.326). Conclusions: This review highlights the need for clear communication within and between healthcare professionals and families; more training for healthcare professionals and improved symptom management planning, including anticipatory prescribing. There is an urgent need for more research into children and young people's experience of symptom management at end-of-life.